An exact solution of a Casson fluid flow induced by dust particles with hybrid nanofluid over a stretching sheet subject to Lorentz forces - Khan, Umair; Mebarek-Oudina, Fateh; Zaib, Aurang; Ishak, Anuar; Abu Bakar, Sakhinah; Sherif, El-Sayed M.; Baleanu, Dumitru (Waves in random and complex media, 2022)
The concept of a hybrid nanofluid has piqued the interest of numerous researchers due to its potential for increased thermal properties, which results in high transfer rates. Hybrid nanofluids are used in heat transport systems such as electronic cooling, and applications in biomedical and pharmaceutical relief. Thus, the present paper inspects the impact of Lorentz forces on the Casson fluid flow of water-based Fe 3 O 4 -MWCNT hybrid nanofluid induced by dust particles from a stretching sheet. The leading PDEs are changed into ODEs by employing similarity variables and then achieving an exact solution for these transformed ODEs. The impacts of distinct physical constraints including fluid interaction particle parameter, Casson parameter, and magnetic parameter on the dust velocity and fluid velocity for normal nanofluid (Fe 3 O 4 /H 2 O) and hybrid nanofluid (Fe 3 O 4 -MWCNT/ H 2 O) are addressed in detail. The present analytic solution shows a strong correlation with earlier published numerical studies in limited cases.